Pengelolaan Arsip Digital dalam Peningkatan Kualitas Pelayanan Publik di Universitas Muhammadiyah Palangkaraya: Digital Archives Management in Improving the Quality of Public Services at Universitas Muhammadiyah Palangkaraya - Arafat, Arafat; Fitriani, Fitriani; Sari, Mita (Anterior Jurnal, 2025)
Nowadays digital archiving has an important role to play in supporting administrative efficiency and the quality of public services, including in higher education institutions. This research discusses the implementation of digital archive management at Universitas Muhammadiyah Palangkaraya (UMPR) as an effort to improve the quality of public services. Through archive digitization, UMPR seeks to speed up the flow of information, facilitate data access, and increase transparency and accountability in administrative services to students, staff, and the relevant community. Even though there are several challenges or obstacles such as limited infrastructure and human resource skills, solutions in the form of training, infrastructure improvements, and system integration can optimize digital archive management. The research results show that digitizing archives at Muhammadiyah University of Palangka Raya has the potential to improve the quality of public services which has an impact on stakeholder satisfaction and makes it easier to carry out administrative tasks as a whole.